Changes in the phytochemical profile of rye bran induced by enzymatic bioprocessing and sourdough fermentation. (November 2016) - Koistinen, Ville Mikael; Katina, Kati; Nordlund, Emilia; Poutanen, Kaisa; Hanhineva, Kati
Abstract: Rye bran is a rich source of phytochemicals, such as alkylresorcinols, benzoxazinoids, and phenolic acids, which likely are attributing to the positive health effects of whole-grain foods. In this study, we examined the effect of two types of bioprocessing of rye bran on the phytochemical profile as compared with non-processed rye bran, using a non-targeted LC–MS metabolomics method. The four breads included in the study were commercial sourdough rye bread baked with 100% rye flour, a white wheat bread, a white wheat bread fortified with native rye bran, and a white wheat bread fortified with bioprocessed rye bran. The changes induced by the combination of enzymatic processing and yeast fermentation in the phytochemical pool were dissimilar to sourdough fermentation. Notably, the amount of free phenolic acids in bran was significantly increased, some of the hexose moieties were released from benzoxazinoids, and alkylresorcinols experienced moderate degradation. The enzymatic bioprocessing increased the bioaccessibility of several phytochemicals, thus making breads fortified with bioprocessed rye bran attractive targets of functional food development. Graphical abstract: Highlights: Bioprocessing changes the phytochemical profile of rye bran. Enzymatic and sourdough processing have different effects on the phytochemicals. New phytochemicals were tentatively identified from rye bran.